Agricultural development and food security in Eastern Europe and Central Asia - Burkitbayeva, Saule; Liefert, William; Swinnen, Johan (International Food Policy Research Institute, 2021)
Although the ECA countries are agriculturally heterogeneous in many ways, they share a common institutional history and, in certain respects, a common reform experience. The economic and institutional transformation that took place in the 1990s and 2000s had a dramatic effect on all these countries. However, the pace of transition from planned to market economy has differed greatly among them. Using a conceptual model, we illustrate and examine the key aspects of the agricultural transition process, some of which are still playing out in various ECA countries. In almost all countries, agricultural output fell substantially during the transition decade of the 1990s, especially in the livestock sector. Key reasons for the decline included the institutional and allocative disruptions and high transaction costs stemming from the move from planned to market economies, as well as the severe reduction in the large subsidies to agriculture under the planned system that maintained high-cost production. A dramatic decline in fertilizer use and crop prices in all ECA countries led to a strong drop in crop yields.